Biaxial strain induced OH engineer for accelerating alkaline hydrogen evolution - Zhang, Tao (2024)
The sluggish kinetics of Volmer step in the alkaline hydrogen evolution results in large energy consumption. The challenge that has yet well resolved is to control the water adsorption and dissociation. Here, we develop biaxially strained MoSe2 three dimensional nanoshells that exhibit enhanced catalytic performance with a low overpotential of 58.2 mV at 10 mA cm−2 in base, and long-term stable activity in membrane-electrode-assembly based electrolyser at 1 A cm−2. Compared to the flat and uniaxial-strained MoSe2, we establish that the stably adsorbed OH engineer on biaxially strained MoSe2 changes the water adsorption configuration from O-down on Mo to O-horizontal on OH* via stronger hydrogen bonds. The favorable water dissociation on 3-coordinated Mo sites and hydrogen adsorption on 4-coordinated Mo sites constitute a tandem electrolysis, resulting in thermodynamically favorable hydrogen evolution. This work deepens our understanding to the impact of strain dimensions on water dissociation and inspires the design of nanostructured catalysts for accelerating the rate-determining step in multi-electron reactions.